The Role of Customary Law in the Formation of Social Identity of Gorontalo Society: An Anthropological Approach - Samsi Pomalingo; Arfan Nusi (Journal of Law, Social Science and Management, 2024)
Introduction: Customary law in Gorontalo is an integral part of the social and cultural life of its society. As one of the regions in Indonesia rich in tradition, Gorontalo has a legal system that is recognized and respected by its community. Customary law not only functions as a set of rules but also serves as a moral and ethical guide in daily interactions. Methods: This research is a qualitative study using an anthropological approach. Data collection techniques include in-depth interviews, observations, and document studies. Data obtained from interviews and observations were analysed using a thematic analysis approach. Results: The research findings indicate that customary law significantly impacts shaping and maintaining the community's social identity in Gorontalo. Customary law in Gorontalo functions as a norm regulating individual behaviour and community members' interactions. Customary law also contributes to the formation of the collective identity of the Gorontalo community. Although customary law has strong traditional roots, research has found that the Gorontalo community can adapt to the changing times. Conclusion: Customary law plays a crucial role in the formation and preservation of the social identity of the Gorontalo community. Through customary law practices, the community not only regulates social life but also preserves and strengthens cultural values that are characteristic of their identity. This research is expected to contribute to a deeper understanding of the relationship between customary law and social identity in the Gorontalo community. Keywords: Customary Law; Gorontalo; Social Identity: Indonesia